Cost Burden of Cancer Screening in Kansas by Region and Rural/Urban Designation - Mills, Kale; Freund, Nicole (Kansas Journal of Medicine, 2025)
Introduction. In 2022, the U.S. healthcare expenditure totaled $4.5 trillion, representing 17.3% of its gross domestic product. Despite this, 26 million Americans remain uninsured, often relying on out-of-pocket payments for essential services like cancer screenings. Kansas, with its high uninsured rate, faces unique challenges, emphasizing the need to analyze the cost burden of these critical yet repeatable interventions.  Methods. Authors of this cross-sectional study analyzed hospital pricing transparency data for breast, lung, and colon cancer screening costs across 124 Kansas hospitals. Data on self-pay costs were collected and compared between urban and rural regions, as well as geographic price variations. Statistical analyses included measures of central tendency, Kruskal-Wallis tests, and Mann-Whitney U tests to evaluate differences. Results. Pricing disparities were evident across Kansas. Urban hospitals charged higher prices for chest computed tomography (CT) scans, while rural hospitals had elevated costs for colonoscopies and mammograms. Notable price variation included Northeast Kansas colonoscopy prices, which ranged from $595 to $11,684. Rural residents faced a greater financial burden, spending 7% of their income on screenings compared to 6% for urban residents. Median screening prices statewide were $2,247 for colonoscopies, $1,109 for chest CT scans, and $228 for mammograms.  Conclusions. These disparities call for targeted policy interventions, such as Medicaid expansion, standardized pricing regulations, and increased support for low-cost clinics. Enhanced hospital pricing transparency is critical for empowering patients and reducing financial burdens. This study highlights the urgent need for equitable access to cancer screenings in Kansas.